NDVI RADIOMETRIC INDEX IN PERMANENT PRESERVATION AREA OBTAINED THROUGH REMOTELY PILOTED AIRCRAFT - Tagliarini, Felipe de Souza Nogueira [UNESP]; Rodrigues, Mikael Timóteo; Rodrigues, Bruno Timóteo; Barros, Ana Clara de [UNESP]; Garcia, Yara Manfrin [UNESP]; Campos, Sérgio [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2021)
The use of Remotely Piloted Aircraft (RPA) as a tool in remote sensing has enabled an operant platform in agricultural and environmental mapping with high precision. This study aimed to analyze the Normalized Difference Vegetation Index (NDVI) in riparian Permanent Preservation Areas (APP) for elaboration of thematic maps through aerophotogrammetry and photointerpretation, with greater detail of vegetation due to the very high spatial resolution achieved with the use of images collected by RPA in a stretch of Lavapés river, inside the domains of Lageado Experimental Farm in the municipality of Botucatu, SP. The images were obtained through MAPIR Survey3W RGB and Survey3W NIR/InfraRED sensors, aboard a 3DR SOLO multirotor RPA. For the construction of RGB and NDVI orthomosaics, the images were processed using Pix4Dmapper app. The NDVI result provided a clear transition among biotic targets (vegetation) and abiotic targets (waterbody), and also among the vegetation itself, with greater vegetative vigor, making possible the distinction of arboreal vegetation, in relation to herbaceous vegetation. The images with high spatial resolution collected by RPA, demonstrated flexibility of use, having high potential to mapping landscape dynamics and the spectral response of vegetation.
ÍNDICE RADIOMÉTRICO NDVI EM ÁREA DE PRESERVAÇÃO PERMANENTE OBTIDO POR MEIO DE AERONAVE REMOTAMENTE PILOTADA
Keywords: aerial photogrammetry; remote sensing; unmanned aerial vehicle; vegetation index